Anthracycline dose optimisation in patients with diffuse large B-cell lymphoma: a multicentre, phase 3, randomised, controlled trial. Issue 6 (June 2019) - Xu, Peng-Peng; Fu, Di; Li, Jian-Yong; Hu, Jian-Da; Wang, Xin; Zhou, Jian-Feng; Yu, Hao; Zhao, Xia; Huang, Yao-Hui; Jiang, Lu; Liu, Feng; Su, Li-Ping; et al.
Summary: Background: Anthracycline dose optimisation in the treatment of diffuse large B-cell lymphoma has rarely been tested. We aimed to find out whether R-CEOP70 was non-inferior to R-CHOP50 with less cardiotoxicity, and whether R-CEOP90 had a superior efficacy to R-CHOP50 or R-CEOP70 with acceptable toxic effects. Methods: In this multicentre, phase 3, randomised, controlled study (NHL-001), patients with newly diagnosed diffuse large B-cell lymphoma or follicular lymphoma grade 3B were enrolled from 20 centres of the Multicenter Hematology–Oncology Programs Evaluation System in China. Young patients (16–60 years) were randomly assigned 1:1:1 (block size of six) to six courses of R-CHOP50, R-CEOP70, or R-CEOP90, and older patients (61–80 years) were assigned 1:1 (block size of four) to R-CHOP50 or R-CEOP70. Patients were randomly assigned using computer-assisted permuted-block randomisation. Investigators and patients were not masked to treatment assignment. In the R-CHOP50 group, patients were given rituximab 375 mg/m 2 intravenously on day 0, cyclophosphamide 750 mg/m 2, doxorubicin 50 mg/m 2, and vincristine 1·4 mg/m 2 (maximum dose 2 mg) intravenously on day 1, and prednisone 60 mg/m 2 (maximum dose 100 mg) orally from day 1–5; in the R-CEOP70 group, epirubicin 70 mg/m 2 replaced doxorubicin; and in the R-CEOP90 group, high dose epirubicin 90 mg/m 2 replaced doxorubicin. All patients received two additional courses of rituximab 375 mg/m 2 intravenously every 21 days. Consolidation radiotherapy was given to patients with bulky disease at diagnosis or residual disease at the end of treatment. The primary endpoint was 2-year progression-free survival. The non-inferiority margin for R-CEOP70 versus R-CHOP50 was defined by hazard ratio [HR] as the upper limit of its 95% CI being no greater than 1·50. Analysis of efficacy and safety were of the intention-to-treat population. This study is registered with ClinicalTrials.gov, number NCT01852435 . Findings: From May 15, 2013, to March 16, 2016, a total of 648 patients were enrolled, including 404 (62%) young patients (R-CHOP50 [n=135], R-CEOP70 [n=134], or R-CEOP90 [n=135]), and 244 (38%) older patients (R-CHOP50 [n=122] or R-CEOP70 [n=122]). Four patients were excluded from the study for consent withdrawal and one patient for misdiagnosis before treatment. The 2-year progression-free survival in the R-CHOP50 group was 72·5% (95% CI 66·6–77·6) and in the R-CEOP70 group was 72·4% ([66·5–77·5]; HR 1·00 [0·73–1·38]; p=0·99). The non-inferiority was met and adverse events were similar between the two groups. Fewer patients in the R-CEOP70 group (14 [13%] of 110) presented with over 10% decrease in left ventricular ejection fraction (LVEF) than those in the R-CHOP50 group (31 [29%] of 108) at 3 years after remission. For young patients, the 2-year progression-free survival in the R-CEOP90 group was 88·8% (82·1–93·1) and was significantly improved compared with the R-CHOP50 group (75·9% [67·7–82·3]; 0·44 [0·25–0·76]; p=0·0047) and the R-CEOP70 group (77·4% [69·4–83·7%]; 0·49 [0·27–0·86]; p=0·017). Grade 3–4 neutropenia occurred more frequently in the R-CEOP90 group (97 [72%] of 134) than in the R-CHOP50 group (87 [65%] of 133) and R-CEOP70 group (84 [63%] of 133) in young patients but without further increase of clinically significant infections. Fewer patients in the R-CEOP70 group (7 [11%] of 66) and in the R-CEOP90 group (10 [13%] of 79) presented with more than 10% decrease in LVEF than those in the R-CHOP50 group (17 [26%] of 66) at 3 years after remission. Interpretation: R-CEOP70 could serve as an alternative regimen to R-CHOP50 with mild long-term cardiotoxicity. Young patients with diffuse large B-cell lymphoma might benefit from high-dose epirubicin. Epirubicin is an alternative drug to doxorubicin in regular R-CHOP with mild long-term cardiotoxicity. Funding: National Natural Science Foundation of China, National Key Research and Development Program, Shanghai Commission of Science and Technology, Shanghai Municipal Education Commission Gaofeng Clinical Medicine Grant Support, Multicenter Clinical Research Project by Shanghai Jiao Tong University School of Medicine, Clinical Research Plan of Shanghai Hospital Development Center, and Chang Jiang Scholars Program.